TILs and Anti-PD1 Therapy: An Alternative Combination Therapy for PDL1 Negative Metastatic Cervical Cancer - Huanhuan Yin; Wei Guo; Xiangling Sun; Ruili Li; Cuihua Feng; Yujie Tan (Journal of Immunology Research)
Background. We investigated the efficacy of TILs and anti-PD1 combination therapy in patients with metastatic cervical cancer with low MSI expression and PDL1-negative. Methods. A total of 80 patients were put on TILs and anti-PD1 combination therapy, and the progression-free survival time (PFS) and overall survival time (OS) were assessed by Kaplan–Meier analysis. Univariate and multivariate analyses were performed to identify factors that could predict the prognosis of metastatic cervical cancer in the previously described patients. Results. The objective response rate was 25%, whereas the mPFS and mOS were 6.1 and 11.3 months, respectively. The therapeutic efficacy was influenced by the characteristics of TILs, infection with HPV, and development of fever just after the therapy. Conclusion. Overall, our results show that the combination therapy of TILs and anti-PD1 significantly improves the prognosis of metastatic cervical cancer.